(untitled) (Journal of Science and Technology Research, 2024)
The Mirzapur industrial area in Bangladesh underwent an assessment for soil contamination with toxic heavy metals such as Cr, Cu, Cd, Pb, & Ni. Pollution in the region attributed to the discharge of industrial wastewater into irrigation canals and lakes. The prevalent contaminants were found to be Cr, Cu, and Ni, followed by Pb and Cd. The geo-accumulation index (Igeo) indicated that the area was classified as experiencing mild to moderate contamination, with Ni exhibiting the highest levels, followed by Cd, Cu, Cr, and Pb. Both the pollution load index (PLI) & contamination factor (CF) showed a moderate level of pollution, while the potential ecological risk index (RI) suggested a moderate ecological risk in this area. The study concluded that the Mirzapur industrial area in Bangladesh exhibited moderate heavy metal contamination, posing a moderate environmental risk. J. of Sci. and Tech. Res. 5(1): 45-52, 2023